Vulnerability evaluation of water inrush in coal seam floor based on zone variable weight and AHP - Zhang Junjie; Liu Shouqiang; Ji Runqing; Zeng Yifan; Liu Xiangyu (矿业科学学报, 2020)
The traditional vulnerability assessment of water inrush from coal seam floor often obtains the constant weight of each influence factor through different models and calculation methods.When evaluating, each subarea adopts this fixed weight, ignoring the fact that the index values of each influence factor in different subareas are in different combinations, and the influence weight should be adjusted accordingly to reflect the relative importance of each influence factor in water inrush from coal seam floor in real time.In this paper, combined with the constant weights of the influence factors determined by AHP, the zoning variable weight model is introduced to adjust the weight distribution of different zones under different combinations of factors, which improves the irrationality of constant weights in different zoning evaluation, further improves the accuracy of evaluation results, and provides some reference for the safe production of coal mines.